Engine Combustion Performance and Emission of a Dual-Fuel NH3-B100 in Yanmar TF-85 - Muayyad Zainal Abidin; Aguk Zuhdi M. Fathallah (International Journal of Marine Engineering Innovation and Research, 2026)
This study investigates the combustion characteristics, engine performance, and emission behavior of an ammonia–biodiesel (NH₃–B100) dual-fuel compression-ignition engine based on a Yanmar TF-85 diesel platform using a combined experimental and numerical approach. Three-dimensional (3D) in-cylinder combustion simulations were performed using ANSYS Forte, while overall engine performance was evaluated through a one-way 3D-1D coupling framework integrated with MATLAB. Baseline single-fuel B100 operation was first validated against experimental measurements, yielding prediction errors below [6%] for engine power, confirming the reliability of the simulation model. After validation, ammonia was introduced through intake manifold injection to establish dual-fuel operation. The results indicate that ammonia substitution delays combustion phasing and reduces the peak heat release rate by approximately [22%], leading to decreases in indicated mean effective pressure and brake power of [30%] and an increase in specific fuel consumption of [30%]. In terms of emissions, carbon-related species were reduced, with CO₂ and CO decreasing by up to [60%] and [50%], respectively, whereas NOₓ emissions increased by [20%], and measurable NH₃ slip was observed under high ammonia energy fractions. Overall, the proposed 3D–1D modeling framework provides an accurate and computationally efficient tool for evaluating ammonia–biodiesel dual-fuel strategies and supports the development of low-carbon marine diesel engines.